Third-degree Price Discrimination in the Presence of Congestion Externality - Achim I. Czerny; Anming Zhang (Tinbergen Institute, 2014)
This paper analyzes third-degree price discrimination of a monopoly airline in the presence of congestion externality when all markets are served. The model features the business-passenger and leisure-passenger markets where business passengers exhibit a higher time valuation, and a less price-elastic demand, than leisure passengers. Our main result is the identification of the time-valuation effect of price discrimination, which can work in the opposite direction as the well-known output effect on welfare. This time-valuation effect clearly explains why discriminating prices can improve welfare even when this is associated with a reduction in aggregate output.
Keywords: D42; L93; 330; Price discrimination; congestion; time valuation; monopoly; airline